Entrepreneurship and multinationals global business and the making of the modern world - Jones, Geoffrey (Edward Elgar Pub. Ltd, 2013)
1. Business enterprises and the making of the modern world -- 2. Entrepreneurs, firms, and global wealth since 1850 -- 3. Globalization and beauty : a historical and firm perspective -- 4. US MNEs in British manufacturing before 1962 -- 5. The Imperial Bank of Iran and Iranian economic development, 1890-1952 -- 6. MNEs, economic development and social change in Asia -- 7. Managing political risk in global business : Beiersdorf 1914-1990 -- 8. Learning to live with governments : Unilever in India and Turkey, 1950-1980 -- 9. The end of nationality? : global firms and borderless worlds
Includes bibliographical references and index
Keywords: Geschichte; Electronic books; International business enterprises; Enterpreneurship; Globalisierung; Multinationales Unternehmen; Entrepreneurship; Aufsatzsammlung